Side-chain modifications of C60 via activation of the easily accessible fulleromalonic acid C61(COOH)2 - Lamparth, Iris; Schick, Georg; Hirsch, Andreas (Liebigs Annalen/Recueil, 1997)
Side-chain modifications of fullerenes can be achieved starting from the malonic acid 2, which is easily accessible by saponification of the corresponding diethyl malonate adduct 1 and is therefore an ideal building block for side chain chemistry on fullerenes. Coupling reactions are carried out via the synthesis of the fullerene active ester 4, which is formed by the reaction of the malonic acid 2 with N-hydroxysuccinimide. During this reaction the malonic acid undergoes decarboxylation, yielding an acetic acid derivative instead of a malonic system. The active ester 4 is isolable and represents an ideal building block for fullerene chemistry. Side-chain modifications can also be carried out as one-step reactions by preparing 4 in situ. We have performed coupling reactions with various compounds containing primary or secondary amino groups. © VCH Verlagsgesellschaft mbH, 1997.